Tahlilan and Yasinan as Phenomenological Expressions of Islamic Religious Experience in Indonesia - Dendy, Dendy Wahyu Anugrah (Universitas Islam Negeri (UIN) Mataram, 2025)
This study examines the traditions of tahlilan and yasinan in Indonesia as concrete expressions of Islamic religious experience through the phenomenological framework of Joachim Wach. Drawing upon a comprehensive library?based methodology, primary analysis focused on Wach’s Ilmu Perbandingan Agama, while secondary sources included SINTA?indexed and international journal articles, dissertations, and prior research on cultural acculturation and religious rituals. Results reveal that tahlilan and yasinan manifest all three dimensions: doctrinal foundations drawn from the Quran, ?ad?th, ijm?‘, and qiy?s; ritual enactments such as collective recitation, charity, and supplication bounded by specific temporal and spatial parameters; and the formation of enduring communal associations that reinforce social cohesion. These traditions not only preserve inherited Islamic values but also adapt dynamically to local socio?cultural contexts, thereby strengthening individual faith and community solidarity. Future research is recommended to adopt multidisciplinary approaches to capture the evolving practices and perceptions surrounding these rituals.